Understanding Gender Perceptions of Long-Distance Romantic Relationships - Vien, Goh Vi; Xu, Cheah Shu (Procedia of Social Sciences and Humanities, 2024)
Lon-distance romantic relationships (LDRRs) were often seen as challenging and unfeasible before the advent of the Internet. Communication was limited to the traditional medium, such as expensive phone calls, letters, and occasional visits, which made it difficult to maintain a relationship. However, with the emergence of new media, communication has become simpler and more accessible, making it easier for people to maintain close connections with their partners, even when separated by distance. To maintain a successful LDRR, it is essential to understand how men and women perceive such relationships. Unfortunately, there are limited studies on gender perceptions and acceptance towards LDRRs. Therefore, this study aims to determine how Malaysian male and female between the age of 20 to 30 years old perceive LDRRs and investigate gender differences in their perception of LDRRs. The data was collected through online semi-structured interviews with six male and six female, and a thematic analysis method was used to analyse the data collected. The study discovered that female participants believed that LDRRs should be independent and that gender characteristics influence the coping mechanisms of couples. On the other hand, male participants believed that physical presence is essential for a relationship and that the coping mechanism is based on personal personality. Nonetheless, both genders acknowledge that communication and sincerity are vital components of LDRRs, and both genders share similar strategies for sustaining the relationship.